Teachers and law of negligence in school sport management in Malaysia - Syed Muhamad Ubaidillah, Syed Husin (Universiti Malaysia Pahang, 2019)
This paper intends to examine the case of negligence of school teachers in dealing with students’ physical safety in school sport activities. As tort liability is a staple of education law, teachers should understand the concept of law of negligence so that they can both protect the rights and ensure the safety of young people. Basically, Malaysian school children spend almost one third of their waking hours in school. Therefore, the potential scope of school liability is broad. The vast majority of injuries to children at school are accidental. However, public perception tends to distort both the extent of school liability and the nature of injuries that children sustain while at school or when engaged in school-based activities.